A study on the preservation and access practices of records in the Local Civil Registry Office of Cainta, Rizal - Amadeo, Elvira N. (2004)
Of the many offices of the Local Government of Cainta, the Local Civil Registry Office was chosen as the subject of this study, since this office produces the bulk of archival records in the local government unit that should be given attention.